2022
DOI: 10.1101/2022.08.31.22279406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell multi-cohort dissection of the schizophrenia transcriptome

Abstract: Schizophrenia is a prevalent mental illness with a high societal burden, complex pathophysiology, and diverse genetic and environmental etiology. Its complexity, polygenicity, and heterogeneity have hindered mechanistic elucidation and the search for new therapeutics. We present a single-cell dissection of schizophrenia-associated transcriptomic changes in the human prefrontal cortex across two independent cohorts, one deeply profiling 48 subjects (361,996 cells), and the other broadly profiling 92 subjects (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 145 publications
(203 reference statements)
5
21
1
Order By: Relevance
“…This result is consistent with previous findings about glia cell abundance in SCZ [16, 17]. A recent snRNA-seq study [18] reporting cellular subpopulations in human brain prefrontal cortex for SCZ vs. healthy controls (Figure 3 (B)) also validated our estimates in Figure 3 (A). However, the CBS RNA deconvolution with signature matrix built from scRNA-seq data of healthy human prefrontal cortex [19] failed to recover the expected case-control disparities or mean abundances in multiple cell types (Figure 3 (C)).…”
Section: Resultssupporting
confidence: 93%
“…This result is consistent with previous findings about glia cell abundance in SCZ [16, 17]. A recent snRNA-seq study [18] reporting cellular subpopulations in human brain prefrontal cortex for SCZ vs. healthy controls (Figure 3 (B)) also validated our estimates in Figure 3 (A). However, the CBS RNA deconvolution with signature matrix built from scRNA-seq data of healthy human prefrontal cortex [19] failed to recover the expected case-control disparities or mean abundances in multiple cell types (Figure 3 (C)).…”
Section: Resultssupporting
confidence: 93%
“…For example, we highlight the interaction between EFNA5 and EPHA5 in excitatory L5/6 and L6 neuron subtypes in deep cortical layers, which is consistent with results from the most recently released SCZ genome-wide association study (GWAS) that identified enrichment of SCZ risk genes in glutamatergic neurons (43). Not only is EFNA5 the locus of a GWAS-identified common SCZ risk variant, but it is also differentially expressed between individuals with SCZ and neurotypical controls in specific cell types (44) . Spatially mapping disease-relevant LR pairs, which are often highly specific and druggable targets, can give new insights into pathophysiology and can help prioritize spatially restricted targets for therapeutic development.…”
Section: Discussionmentioning
confidence: 99%
“…To compare deconvoluted PAGs and PAGs from sc/snRNAseq data, PAGs for AD( 23 ) and SCZ( 59 ) in cell types were downloaded. For brain development, PAGs were identified in pseudo-bulk data.…”
Section: Methodsmentioning
confidence: 99%